STRATEGI PERSONALISASI KONTEN DIGITAL DALAM MENINGKATKAN CUSTOMER LOYALTY DI E-COMMERCE INDONESIA - Uning Heri Gagarin; Hendri Mayanta; Evlin Anariska Sebayang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines digital content personalization strategies to enhance customer loyalty in Indonesian e-commerce, an industry experiencing rapid growth yet facing major retention challenges (high churn). The study aims to analyze the level of implementation, the impact of personalization, key factors affecting its effectiveness, the mechanism linking personalization to loyalty, and to develop an actionable framework tailored to the Indonesian context. Using a mixed-methods design with a sequential explanatory approach, the research includes a quantitative phase (survey of 500 respondents) and a qualitative phase (in-depth interviews, case studies, expert interviews, and focus group discussions). The findings indicate that digital content personalization significantly affects customer loyalty with a total effect of β = 0.45. β=0.45, mediated by perceived relevance, customer satisfaction, and trust in brand. The results further highlight the importance of data quality, as well as the moderating roles of privacy concerns and customer involvement. In addition, real-time personalization and omnichannel integration are more effective than batch approaches. The study proposes the Indonesian E-commerce Personalization Framework (IEPF) structured around four pillars (Data Foundation, Technology Enablement, Content Strategy, and Measurement & Optimization) and estimates an average ROI of 382%. The research implies that effective personalization depends not only on technology, but also on understanding consumers’ behaviors and privacy concerns.